2023
DOI: 10.1002/aenm.202300574
|View full text |Cite
|
Sign up to set email alerts
|

3D Macroporous Frame Based Microbattery With Ultrahigh Capacity, Energy Density, and Integrability

Abstract: In-plane microbatteries (MBs) with features of facile integration, mass customization, and especially superior electrochemical performance are urgently required for self-powered microelectronic devices. In this work, a facile manufacturing process is employed to fabricate Zn-MnO 2 MB with a 3D macroporous microelectrode. Benefiting from the high electron/ion transport path of 3D macroporous microelectrode and high mass-loading of poly(3,4-ethylenedioxythiophene)-manganese dioxide (PEDOT-MnO 2 ) film, the MB ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…At 0.3 mA cm –2 , areal device capacities reached 4.82, 7.93, and 11.93 mA h cm –2 for 1, 2, and 3 printing layers, respectively. The achieved device capacity values were superior to those of most reported Zn-based battery devices and even Li-based battery devices. It can be observed that the 3DP-NiVO//NHCs@Zn battery exhibited a high energy density of up to 5.98 mW h cm –2 , which was superior to those of reported micro energy storage devices (Figure d). ,, …”
Section: Resultsmentioning
confidence: 86%
“…At 0.3 mA cm –2 , areal device capacities reached 4.82, 7.93, and 11.93 mA h cm –2 for 1, 2, and 3 printing layers, respectively. The achieved device capacity values were superior to those of most reported Zn-based battery devices and even Li-based battery devices. It can be observed that the 3DP-NiVO//NHCs@Zn battery exhibited a high energy density of up to 5.98 mW h cm –2 , which was superior to those of reported micro energy storage devices (Figure d). ,, …”
Section: Resultsmentioning
confidence: 86%
“…In this electroplating method, the pre‐deposited thickness of Cu coating and the mass loading of NiCo BOH are key factors of deciding the performance of final battery. The other common cathode materials, like MnO 2 , PANI, and PPy, can also be prepared by this method under a mild condition, [ 29,79,80,94,95 ] and the pH and components of solution system play a significant role in regulating their morphologies and microstructures. In addition, carbon cloth is often used as the current collector for electroplating in flexible energy‐storage devices, [ 96–98 ] and can achieve a good stretchability using a kirigami structure.…”
Section: Stretchable Componentsmentioning
confidence: 99%
“…This leads to higher capacity and energy compared to 2D micro-devices. 202 Additionally, the hierarchical structure of the μE arrays in 3D allows for faster diffusion of electrolyte ions, resulting in higher power and energy density. 3D stacked μBs can maximize the use of the electrode area, leading to increased active material loading and capacity compared to 2D stacked μBs.…”
Section: Microelectrodes In Different Configuration Design Of Sodium-...mentioning
confidence: 99%